Attitudes of Young School Aged Childrens to the Teaching of Physical Education - Milena Mitrovic; Katarina Dragutinovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2019)
Physical Education as an school subject has a great influence on the development of psycho-physical abilities of children. In view of this, it is important to know what the attitude of students towards the teaching of Physical Education is. The aim of our research was to determine exactly what the attitudes of the junior schoolchildrens toward the teaching of Physical Education are in the function of improving or changing the teaching process. We tried to answer the question using anonymous standardized questionnaires adapted to this research. The research involved 327 students of the 4th and 5th grade primary schools from Podgorica and Niksic. The results showed that almost all students are eager to attend classes of Physical Education, which they are very pleased to consider contributing to their health and physical development, as well as the development of friendship, strength, care, value and endurance. Most students believe that Physical Education is as important as other subjects, and that Physical Education is best performed in a schoolroom. A large number of pupils would also not change anything compared to the previous lessons. As far as favorite sports are concerned boys traditionally prefer to play football, while girls are more oriented towards volleyball, handball, rhythmic and gymnastics.